Association of Autism Spectrum Disorders With Neonatal Hyperbilirubinemia. (21st July 2015) - Lozada, Luis E.; Nylund, Cade M.; Gorman, Gregory H.; Hisle-Gorman, Elizabeth; Erdie-Lalena, Christine R.; Kuehn, Devon
Autism spectrum disorders (ASD) are a common neurodevelopmental disorder of unknown etiology. Studies suggest a link between autism and neonatal jaundice. A 1:3 matched case–control study was conducted with children enrolled in the Military Health System born between October 2002 and September 2009. Diagnostic and procedure codes were used for identifying ASD and hyperbilirubinemia. Two definitions for hyperbilirubinemia were evaluated: an inpatient admission with a diagnosis of jaundice and treatment with phototherapy. A total of 2917 children with ASD and 8751 matched controls were included in the study. After adjustment, there remained an association between ASD in children and an admission with a diagnosis of jaundice (odds ratio = 1.18; 95% confidence interval = 1.06-1.31; P = .001) and phototherapy treatment (odds ratio = 1.33; 95% confidence interval = 1.04-1.69; P = .008). Children who develop ASD are more likely to have an admission with a diagnosis of jaundice in the neonatal period and more likely to require treatment for this jaundice.